Optimized design of the pneumatic precision seed-metering device for carrots - Feng, Dinghao; Sun, Xinping; Li, Hua; Qi, Xindan; Wang, Yongjian; Mbugua, Nyambura Samuel (International Journal of Agricultural and Biological Engineering, 2024)
The small size, light weight, irregular shape, and impurities that characterize seed groups increase clogging tendencies in the traditional seed-metering device thereby making it difficult to achieve high-speed precision seeding. A pneumatic seed-metering device with good seed-filling performance for carrot was designed in this study. By analyzing the movement state of seeds in the device under the theoretical condition, it was concluded that the minimum critical negative pressure value of air chamber was 0.32 kPa, which provided a theoretical basis for simulation and testing. ANSYS 17.0 Software was used to simulate the shape of the seeding plate hole. By comparing the pressure, air flow stability between the suction surface and the plug removal surface of the convection field, it was concluded that the conical hole was optimal. A bench verification test was conducted on the device. The average qualified rate, missing rate, and replaying rate were 81.48%, 4.07%, and 14.45%, respectively, which provided a strong reference for the design of carrot precision seed-metering device. Keywords: seed-metering device, carrot, precision seeding, bench verification test DOI: 10.25165/j.ijabe.20231606.7911 Citation: Feng D H, Sun X P, Li H, Qi X D, Wang Y J, Nyambura S M. Optimized design of the pneumatic precision seed-metering device for carrots. Int J Agric & Biol Eng, 2023; 16(6): 134–147.